Encapsulating material for compounds having non-stoichiometric composition and method for producing the same

JP7637942B2Active Publication Date: 2025-03-03THE UNIV OF TOKYO +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021029328
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-25
Publication Date
2025-03-03
Estimated Expiration
2041-02-25

AI Technical Summary

Benefits of technology

【0013】 本発明により、非化学量論組成を有する化合物に適した封止材を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637942000005
    Figure 0007637942000005
  • Figure 0007637942000006
    Figure 0007637942000006
  • Figure 0007637942000007
    Figure 0007637942000007
Patent Text Reader

Abstract

To provide an encapsulant suitable for a compound having a non-stoichiometric composition.SOLUTION: An encapsulant for a compound including a non-stoichiometric composition includes a polymer layer and an inorganic oxide insulator layer, and the polymer layer includes a first polymer layer having an organic solvent soluble polymer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sealing material for a compound having a non-stoichiometric composition and a method for producing the same. [Background technology]

[0002] Semiconductor devices are expected to be the basic elements of electronic devices in the Internet of Things (IoT) society. In particular, amorphous metal oxide semiconductors (AOS) are promising candidates for printed electronics.

[0003] AOS has features such as high mobility, low-voltage driving, high affinity with gate insulating films, transparency, and high thermal stability, and is expected to be applied to next-generation devices such as transparent and flexible TFTs and electronic paper.

[0004] In addition, the use of printed electronics is a promising method due to its high throughput. In particular, thin-film transistors (TFTs) using printable semiconductors are attracting attention as key devices for developing trillions of sensors and high-frequency identification tags, enabling information exchange between different objects. Among printable materials, amorphous metal oxide semiconductors (AOS), which have high carrier mobility and excellent uniformity, are considered promising as printing materials for TFTs.

[0005] However, AOS is highly sensitive to the environment, including oxygen and water, and its mobility, threshold voltage, bias stress, etc. are unstable, which makes it difficult to achieve practical long-term stable operation and degradation during the manufacturing process. Therefore, to protect the AOS, a sealant (passivation) is used to suppress the effects of surrounding molecules, including oxygen and water, on the AOS.

[0006] Insulating inorganic oxide encapsulants such as SiOx, SiOx / SiNx, AlOx, and YOx exhibit low gas and water permeability. However, when a film formation process such as atomic layer deposition (ALD) or sputtering is used to form such inorganic oxide encapsulants, the AOS may be damaged, resulting in a decrease in TFT performance.

[0007] Alternatively, insulating polymers formed by chemical vapor deposition (CVD), such as CYTOP (registered trademark) and parylene, are also used as encapsulants (Patent Document 1). These are formed by a relatively mild CVD film formation process, so they cause relatively little damage to AOS. However, such polymers have a higher gas and water permeability than inorganic oxides, so their protective performance is insufficient.

[0008] For this reason, a sealing material having a two-layer structure that combines the above sealing materials has been proposed. Non-Patent Document 1 proposes a technology in which an organic parylene layer is formed, and then an inorganic oxide insulator layer, AlOx, is laminated by the ALD method to perform sealing. [Prior art documents] [Non-patent literature]

[0009] [Non-Patent Document 1] S. Zhan et al., Phys. Status Solidi, 2020, 217, 1900832. Summary of the Invention [Problem to be solved by the invention]

[0010] These conventional encapsulants can be used for amorphous metal oxide semiconductors (AOS) formed by vacuum processes, but they were found to damage AOS when used with AOS formed by printable solution processes. The reason for this is that AOS formed by solution processes have a non-stoichiometric composition with oxygen and other defects, making them highly environmentally sensitive and easily damaged by the formation process of conventional encapsulants.

[0011] Therefore, there is a demand for a sealing technique suitable for compounds having non-stoichiometric compositions. [Means for solving the problem]

[0012] The gist of the present invention is as follows. (1) a polymer layer and an inorganic oxide insulator layer; The polymer layer comprises a first polymer layer comprising an organic solvent soluble polymer; Encapsulant for compounds with non-stoichiometric composition. (2) the polymer layer further includes a second polymer layer located between the first polymer layer and the inorganic oxide insulator layer; The second polymer layer is made of a chemical vapor deposition film. The sealing material according to (1) above. (3) The encapsulant according to (2) above, wherein the total thickness of the first polymer layer, the second polymer layer, and the inorganic oxide insulator layer is 100 nm or less. (4) The sealing material according to any one of the above (1) to (3), wherein the organic solvent-soluble polymer is an acrylic polymer, a styrene polymer, a fluorine-based polymer, a thermally crosslinkable polymer, or a combination thereof. (5) The sealing material according to any one of (1) to (4) above, wherein the inorganic oxide insulator of the inorganic oxide insulator layer is AlOx, HfOx, ZrOx, SiOx, TiOx, or a combination thereof. (6) The sealing material according to any one of (2) to (5) above, wherein the chemical vapor deposition film is parylene. (7) The sealing material according to any one of the above (1) to (6), wherein the compound having a non-stoichiometric composition is an amorphous metal oxide inorganic semiconductor film. (8) The encapsulant according to (7) above, wherein the amorphous metal oxide inorganic semiconductor film has a different distribution of oxygen vacancies in a direction perpendicular to a main surface of the film, with the surface having more oxygen vacancies than the interior. (9) An electronic device comprising the sealing material according to any one of (1) to (8) above. (10) providing a substrate; preparing an organic solvent having a first polymer dissolved therein; applying an organic solvent having the first polymer dissolved therein onto the substrate to form a polymer layer including a first polymer layer; and On the polymer layer, an inorganic oxide insulator layer is formed by atomic layer deposition or sputtering to obtain an encapsulant. A method for producing an encapsulant for a compound having a non-stoichiometric composition, comprising: (11) The forming of the polymer layer includes forming a second polymer layer, which is a chemical vapor deposition film, on the first polymer layer by using a chemical vapor deposition method; forming the inorganic oxide insulator layer includes forming the inorganic oxide insulator layer on the second polymer layer. A method for producing the encapsulant according to (10) above. Effect of the Invention

[0013] According to the present invention, it is possible to provide a sealing material suitable for compounds having a non-stoichiometric composition. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a schematic cross-sectional view of the sealing material of the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view of the sealing material of the present disclosure disposed so as to be in contact with a compound having a non-stoichiometric composition. [Diagram 3]FIG. 3 is a cross-sectional schematic diagram of an encapsulant having a first polymer layer, a second polymer layer, and an inorganic oxide insulator layer. [Figure 4] FIG. 4 is a schematic cross-sectional view of a TFT prepared in the example. [Diagram 5] FIG. 5 is a schematic cross-sectional view of a TFT prepared in the example. [Figure 6] FIG. 6 is an optical microscope photograph of the TFT fabricated in the example. [Figure 7] FIG. 7 is a graph showing the transfer characteristics of the TFT fabricated in the comparative example. [Figure 8] FIG. 8 is a graph showing the transfer characteristics of the TFTs fabricated in the example and the comparative example. [Figure 9] FIG. 9 is a graph showing the transfer characteristics of the TFT fabricated in the comparative example before and after water treatment. [Figure 10] FIG. 10 is a graph showing the results of measuring the bias stress stability of the TFTs fabricated in the examples and the comparative examples. [Figure 11] FIG. 11 is a graph showing an estimation of the Vth shift value (ΔVth) by measuring the transfer characteristics before and after the bias stress of the TFTs fabricated in the examples and the comparative examples. [Figure 12] FIG. 12 is a graph showing the measurement results of the transfer characteristics of the TFT fabricated in the comparative example. [Figure 13] FIG. 13 shows the results of film thickness evaluation by X-ray reflectance measurement of the PMMA layer formed in the comparative example. [Figure 14] FIG. 14 is an AFM measurement image of the IZO layer produced in the example. [Figure 15] FIG. 15 is an AFM measurement image of the PMMA layer produced in the example. [Figure 16] FIG. 16 is a schematic diagram showing a method for preparing a precursor solution of an amorphous metal oxide inorganic semiconductor (AOS) using a sol-gel method. [Figure 17] FIG. 17 is a schematic diagram showing a method for forming an AOS layer by using a spin coating method. [Figure 18] FIG. 18 shows the results of angle-resolved XPS measurements of O1s. [Figure 19] FIG. 19 is a graph showing the angle dependence of the ratio (ηM-OM) of MOM (metal oxide state) to the total O1s. [Figure 20] FIG. 20 is a schematic diagram of the angle-resolved XPS measurement method. [Figure 21] FIG. 21 is a schematic cross-sectional view showing the distribution of oxygen vacancies depending on the thickness of the AOS film. [Figure 22] FIG. 22 is a graph showing the thickness dependence of the ratio of each bond type to the total O1s from the substrate toward the outermost surface of the AOS film. [Diagram 23] FIG. 23 is a graph showing the initial characteristics of the TFTs produced in the examples, measured immediately after production, and the characteristics after being left in the air for 20 months. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present disclosure is directed to an encapsulant for compounds having non-stoichiometric compositions, comprising a polymer layer and an inorganic oxide insulator layer, the polymer layer comprising a first polymer layer comprising an organic solvent soluble polymer.

[0016] The encapsulant of the present disclosure can suppress damage to a compound having a nonstoichiometric composition even in an atmosphere containing moisture and oxygen, and therefore allows an electronic device including a compound having a nonstoichiometric composition to stably operate in the atmosphere for a long period of time.

[0017] The encapsulant of the present disclosure can also suppress damage to the compound having a nonstoichiometric composition caused by the process of disposing the encapsulant or the process of fabricating an electronic element or device thereafter. For example, even if another electronic element or device is stacked and integrated on the encapsulant by a lithography process using water or an organic solvent after the encapsulant is formed, the deterioration of the compound having a nonstoichiometric composition can be suppressed. Therefore, the encapsulant of the present disclosure can make it possible to fabricate complex integrated devices including a compound having a nonstoichiometric composition, such as complementary metal oxide semiconductors and inorganic / organic hybrid semiconductors. The encapsulant of the present disclosure can provide simple and effective encapsulation, particularly in printed electronics.

[0018] FIG. 1 shows a schematic cross-sectional view of an encapsulant 100 of the present disclosure. The encapsulant 100 includes a polymer layer 10 and an inorganic oxide insulator layer 20. The polymer layer 10 includes a first polymer layer including an organic solvent soluble polymer. The polymer layer 10 may be composed of only the first polymer layer. The first polymer layer is preferably made of an organic solvent soluble polymer. The organic solvent soluble polymer means a polymer that is soluble in an organic solvent, and includes those that are polymers or oligomers when dissolved in an organic solvent. The organic solvent is a solvent that can dissolve the organic solvent soluble polymer and does not dissolve a compound having a non-stoichiometric composition, and examples thereof include butyl acetate, toluene, xylene, acetonitrile, and the like.

[0019] The first polymer layer containing an organic solvent-soluble polymer can be formed by a mild method called solution processing. The solution process does not use vacuum or radical reactions, so it is possible to avoid further formation of oxygen defects due to oxygen elimination, and has the advantage of being very low reactivity with compounds having non-stoichiometric compositions. The solution process does not involve reactions that generate acids. Therefore, the first polymer layer can be formed directly on the compound having non-stoichiometric compositions without causing substantial damage.

[0020] FIG. 2 shows a schematic cross-sectional view of the encapsulant 100 of the present disclosure disposed so as to contact the compound layer 30 having a nonstoichiometric composition. The encapsulant 100 may be used such that the polymer layer 10 of the encapsulant 100 is located on the side of the compound layer 30 having a nonstoichiometric composition contained in the electronic device, and the inorganic oxide insulator layer 20 is located on the opposite side to the compound layer 30 having a nonstoichiometric composition. In FIG. 2, the polymer layer 10 of the encapsulant 100 is disposed so as to contact the compound layer 30 having a nonstoichiometric composition, but another layer may be present between the polymer layer 10 of the encapsulant 100 and the compound layer 30 having a nonstoichiometric composition, and the polymer layer 10 of the encapsulant 100 and the compound layer 30 having a nonstoichiometric composition may not be in direct contact with each other. For example, when the encapsulant of the present disclosure is used as an encapsulant for a thin-film solar cell, the compound layer having a nonstoichiometric composition is located inside the intermediate layer of the thin-film solar cell, and other materials or electrodes may be laminated on the compound layer having a nonstoichiometric composition.

[0021] In this way, the presence of the polymer layer 10 between the compound layer 30 having a non-stoichiometric composition and the inorganic oxide insulator layer 20 can suppress damage to the compound having a non-stoichiometric composition when forming the inorganic oxide insulator layer 20.

[0022] Conventionally, inorganic oxide insulator layers such as AlOx layers have been formed directly on the material to be sealed and used as sealing materials. However, when attempting to directly form an inorganic oxide insulator layer using atomic layer deposition (ALD) on a compound having a nonstoichiometric composition such as IZOx produced by a solution process, the compound having a nonstoichiometric composition will deteriorate because the ALD method involves heating the substrate in a vacuum and using water. When attempting to directly form an inorganic oxide insulator layer using sputtering on a compound having a nonstoichiometric composition such as IZOx produced by a solution process, the compound having a nonstoichiometric composition will deteriorate because the sputtering method is a vacuum process.

[0023] Since chemical vapor deposition films (evaporated films) such as parylene can be formed by chemical vapor deposition (CVD), which is relatively milder than ALD and does not require substrate heating, chemical vapor deposition films such as parylene are also formed as a base for forming inorganic oxide insulating layers. However, compounds with non-stoichiometric compositions are highly sensitive to the environment, and are therefore easily damaged by the vacuum environment and the radicals generated during the formation of the chemical vapor deposition film.

[0024] In contrast, by forming a first polymer layer containing an organic solvent-soluble polymer on a compound having a non-stoichiometric composition by a solution process, the polymer layer can be disposed without causing substantial damage to the compound having a non-stoichiometric composition.

[0025] The first polymer layer can protect the compound having a nonstoichiometric composition from moisture accompanying the ALD method or the vacuum environment of the sputtering process. Therefore, an inorganic oxide insulator layer can be formed on the polymer layer without substantially damaging the compound having a nonstoichiometric composition. The first polymer layer has a low density and therefore a low gas barrier performance, allowing oxygen to permeate to a certain extent. The density of the first polymer layer is preferably 0.4 to 1.3 g / cm. 3 , more preferably 0.5 to 1.2 g / cm 3 , and more preferably 0.6 to 1.1 g / cm 3 , and more preferably 0.7 to 1.0 g / cm 3 On the other hand, since a dense inorganic oxide insulator layer is located on the first polymer layer, moisture and oxygen cannot pass through the encapsulant. The density of the first polymer layer is calculated from X-ray reflectivity measurement. By fitting the X-ray reflectivity data, the film thickness and film density can be estimated simultaneously as fitting parameters.

[0026] Examples of compounds having a non-stoichiometric composition include amorphous metal oxide inorganic semiconductors (AOS), metal chalcogenides, halide perovskites, etc. Examples of AOS include ZnO, In2O3, In-Zn-O (IZO), In-Ga-Zn-O (IGZO), and especially AOS formed by solution process. Examples of metal chalcogenides include layered materials such as molybdenum sulfide, tungsten sulfide, and molybdenum selenide, and quantum dots such as lead sulfide and cadmium sulfide. Examples of halide perovskites include organic-inorganic hybrid materials or inorganic metal materials represented by ABX3, A2BX4 (A is an organic ammonium material or an alkali metal, B is a metal such as lead or tin, and X is a halogen element). It can be confirmed whether the AOS layer is amorphous by thin-film X-ray diffraction.

[0027] Examples of electronic devices including a compound having a nonstoichiometric composition include transistors, complementary metal oxide semiconductor devices, organic electroluminescence (organic EL), batteries, organic solar cells, oxide sensors, etc. Transistors include thin film transistors, field effect transistors, etc. Oxide sensors include chemical sensors, optical sensors, etc. The same applies below.

[0028] The encapsulant of the present disclosure may be in any shape and may be an encapsulating film, an encapsulating sheet, or the like.

[0029] The first polymer layer has a thickness of preferably 50 nm or more, more preferably 75 nm or more, and even more preferably 100 nm or more. When the first polymer layer has the preferred thickness, damage to the compound having a nonstoichiometric composition during the formation of the inorganic oxide insulator layer can be further suppressed. The upper limit of the thickness of the first polymer layer is not particularly limited, but the thickness of the first polymer layer is preferably 1000 nm or less, more preferably 500 nm or less, and may be 100 nm or less, 50 nm or less, or 30 nm or less so that the thickness of the electronic device including the encapsulant does not increase.

[0030] Preferably, the polymer layer further comprises a second polymer layer located between the first polymer layer and the inorganic oxide insulator layer, the second polymer layer being comprised of a chemical vapor deposition film.

[0031] The second polymer layer made of a chemical vapor deposition film is located between the first polymer layer and the inorganic oxide insulator layer, so that damage to the compound having a nonstoichiometric composition during the formation of the inorganic oxide insulator layer can be suppressed. In addition, the compound having a nonstoichiometric composition can be protected from the attack of radicals caused by the CVD process for forming the second polymer layer. When the polymer layer includes the second polymer layer, the preferred thickness of the first polymer layer may be thin or may be 10 nm or more.

[0032] 3 shows a schematic cross-sectional view of an encapsulant 100 having a first polymer layer 12, a second polymer layer 14, and an inorganic oxide insulator layer 20. The encapsulant 100 includes a second polymer layer 14 located between the first polymer layer 12 and the inorganic oxide insulator layer 20.

[0033] In the hybrid structure encapsulant 100 including the first polymer layer 12, the second polymer layer 14, and the inorganic oxide insulator layer 20, the first polymer layer 12 including an organic solvent soluble polymer and the second polymer layer 14 consisting of a chemical vapor deposition film function as a buffer layer against damage caused by the ALD process or sputtering process when forming the inorganic oxide insulator layer 20, and the inorganic oxide insulator layer 20 has a strong barrier effect.

[0034] Unlike the first polymer layer formed by a solution process, the chemical vapor deposition film is formed by a dry process. Therefore, the second polymer layer is dense and has a high barrier effect because it is composed of a chemical vapor deposition film. The density of the second polymer layer composed of a chemical vapor deposition film is higher than the density of the first polymer layer containing an organic solvent soluble polymer. The density of the second polymer layer is preferably 1.0 to 1.5 g / cm. 3 , more preferably more than 1.0 to 1.45 g / cm 3The density of the second polymer layer is measured by ASTM D1505 or ASTM E1461.

[0035] The thickness of the second polymer layer made of a chemical vapor deposition film is preferably 10 to 40 nm, more preferably 15 to 35 nm. Since the second polymer layer has a high density, it can obtain a barrier effect even in the above preferred thickness range, and therefore the overall thickness of the encapsulant can be reduced.

[0036] The thickness of the inorganic oxide insulator layer is preferably 5 to 100 nm, more preferably 15 to 75 nm, and even more preferably 25 to 55 nm. The inorganic oxide insulator layer has a higher barrier effect than the polymer layer, which is an organic film, and therefore, within the above preferred thickness range, the overall thickness of the encapsulant can be reduced while still exhibiting a good barrier effect. Since the inorganic oxide insulator layer has a dense structure and is relatively hard, the thickness of the inorganic oxide insulator layer is preferably 100 nm or less from the viewpoint of ensuring the flexibility of the electronic element or electronic device including the encapsulant.

[0037] When the encapsulant includes a first polymer layer containing an organic solvent-soluble polymer, a second polymer layer made of a chemical vapor deposition film, and an inorganic oxide insulator layer, the total thickness of the encapsulant is preferably 100 nm or less, more preferably 90 nm or less, and even more preferably 80 nm or less. When the encapsulant includes a second polymer layer made of a chemical vapor deposition film, the total thickness of the encapsulant can be reduced. The lower limit of the thickness of the encapsulant is preferably 25 nm or more, more preferably 40 nm or more. By having the thickness of the encapsulant in the above preferred range, the thickness of the electronic element or electronic device including the encapsulant can be reduced while obtaining a good barrier function.

[0038] The organic solvent-soluble polymer is preferably an acrylic polymer, a styrene-based polymer, a fluorine-based polymer, a thermally crosslinkable polymer, or a combination thereof.

[0039] The acrylic polymer is preferably polymethylmethacrylate (PMMA), polyadamantylmethacrylate (PADMA), or polycyclohexylmethacrylate (PCMA).

[0040] The styrenic polymer is preferably polystyrene, poly-α-methylstyrene (PαMS), poly-4-methylstyrene (PMS), or polyvinylphenol (PVP).

[0041] The fluoropolymer is preferably CYTOP® or Teflon® AF.

[0042] The thermally crosslinkable polymer is preferably an epoxy resin or a thermosetting cycloolefin polymer.

[0043] The inorganic oxide insulator of the inorganic oxide insulator layer is preferably AlOx, HfOx, ZrOx, SiOx, TiOx, or a combination thereof. x may be a value that satisfies the stoichiometric composition or may not satisfy the stoichiometric composition. The inorganic oxide insulator layer has a high density and cannot be permeated by large molecules such as water molecules and oxygen in the air, so it has a high barrier effect against moisture and gas.

[0044] The chemical vapor deposition film is preferably parylene. Parylene is preferred because it is formed sequentially at about room temperature and has high density and uniformity. Parylene also includes its derivatives.

[0045] The encapsulant preferably has a three-layer hybrid structure of a PMMA layer as a first polymer layer, a parylene layer as a second polymer layer, and an AlOx layer as an inorganic oxide insulator layer. The PMMA / parylene / AlOx hybrid three-layer encapsulation film can provide strong protection without degrading the performance of compounds with non-stoichiometric compositions.

[0046] The compound having a non-stoichiometric composition is preferably an amorphous metal oxide inorganic semiconductor (AOS) film. As shown in FIG. 21, the AOS film preferably has a different distribution of oxygen vacancies in the direction perpendicular to the main surface of the AOS film, with the surface having more oxygen vacancies than the interior.

[0047] The distribution of oxygen vacancies in the thickness direction of the AOS layer was measured by angle-resolved X-ray photoelectron spectroscopy (XPS), which was used to measure the ratio of MOM (metal oxide) to the total O1s (η M-O-M ) can be evaluated. In an AOS layer having a distribution of oxygen vacancies in the thickness direction, the closer to the outermost surface of the AOS layer, the fewer the MOM (M:In or Zn) bonds.

[0048] As shown in FIG. 20, angle-resolved XPS is a method of measuring the intensity of a sample by changing the angle (tilt angle θ) of the XPS detector (analyzer) relative to the vertical direction of the surface of the measurement sample as the reference (0°), as shown in the following formulas 1 and 2:

number

number

[0049] The AOS layer is the inner η M-O-M η of the top surface M-O-Mis preferably smaller by 10% or more, more preferably by 15% or more, and further preferably by 20% or more.

[0050] The encapsulant of the present disclosure can be used for electronic elements. The encapsulant of the present disclosure can be used as an encapsulant for covering electronic elements, preferably arranged on a flexible substrate, that contain a compound having a non-stoichiometric composition. Examples of electronic devices that contain electronic elements include transistors, complementary metal oxide semiconductor devices, organic electroluminescence (EL), batteries, solar cells, and oxide sensors.

[0051] The present disclosure is also directed to a method for producing an encapsulant for a compound having a non-stoichiometric composition, comprising: providing a substrate; preparing an organic solvent having a first polymer dissolved therein; applying the organic solvent having the first polymer dissolved therein onto the substrate to form a polymer layer comprising a first polymer layer; and forming an inorganic oxide insulator layer on the polymer layer by atomic layer deposition or sputtering to obtain an encapsulant.

[0052] In this method, an organic solvent in which a first polymer is dissolved is prepared. The organic solvent and the first polymer can be mixed to prepare the organic solvent in which the first polymer is dissolved. The concentration of the first polymer may be changed depending on the intended thickness of the first polymer layer, and is, for example, 1 to 80 mg / mL, 2 to 70 mg / mL, or 3 to 60 mg / mL.

[0053] In this method, an organic solvent in which a first polymer is dissolved is applied onto a substrate to form a polymer layer including a first polymer layer. The application method is preferably a spin coating method, a bar coating method, a spray coating method, a dip coating method, an inkjet method, a flexographic printing method, or a gravure printing method, more preferably a spin coating method, a bar coating method, a spray coating method, a dip coating method, or an inkjet method, and even more preferably a spin coating method.

[0054] The inorganic oxide insulator layer is formed by atomic layer deposition (ALD) or sputtering, preferably atomic layer deposition (ALD). The ALD method is preferred in that it can form a film over a large area and reduce costs.

[0055] The deposition temperature of the inorganic oxide insulator layer is preferably 200° C. or less, more preferably 150° C. or less, and even more preferably 125° C. or less. By depositing the layer within the above-mentioned preferred temperature range, layers below the inorganic oxide insulator layer are less likely to be damaged. In particular, since flexible substrates are made of organic materials such as polyethylene terephthalate (PET) and polyimide, deposition within the above-mentioned preferred temperature range can prevent the substrate from being damaged.

[0056] Preferably, forming the polymer layer includes forming a second polymer layer, which is a chemical vapor deposition film, on the first polymer layer using chemical vapor deposition (CVD), and forming the inorganic oxide insulator layer includes forming an inorganic oxide insulator layer on the second polymer layer.

[0057] The second polymer layer, which is a chemical vapor deposition film, is deposited by CVD, which is a light vacuum process and is favorable in terms of deposition speed, processing area, density, and uniformity.

[0058] The contents regarding the above-mentioned sealing material are applied to the polymer layer, the first polymer layer, the second polymer layer, the inorganic oxide insulator layer, the organic solvent-soluble polymer, the organic solvent, and other components. EXAMPLES

[0059] Example 1 (Fabrication of TFT with two-layer encapsulant and IZO) (Preparation of AOS precursor solution by sol-gel method) A precursor solution of indium zinc oxide (IZO) was prepared by the sol-gel method shown in FIG. 16. 0.462 g of In(NO3)3-xH2O (Aldrich) was added to 10 mL of 2-methoxyethanol and stirred in air for 6 hours to obtain an indium precursor solution (0.1 M). 0.297 g of Zn(NO3)2-xH2O (Aldrich) was added to 10 mL of 2-methoxyethanol and stirred in air for 6 hours to obtain a zinc precursor solution (0.1 M). The obtained indium and zinc precursor solutions were mixed in a molar ratio of In:Zn=3:2 and stirred in air for 6 hours to prepare an IZO precursor solution.

[0060] A P-doped Si wafer substrate having a thermally oxidized SiO2 (thickness 100 nm) as a gate insulating film was ultrasonically cleaned in acetone and then 2-propanol for 10 minutes each, and then dried at 100°C for 10 minutes in air using a hot plate.

[0061] (Formation of AOS layer) The above-mentioned washed and dried substrate was treated with a UV ozone cleaner (UV253H, manufactured by Filgen) for 10 minutes to remove organic residues and improve wettability.

[0062] As shown in Fig. 17, the prepared IZO precursor solution was spin-coated on the UV-treated substrate at 500 rpm for 5 seconds, then at 5000 rpm for 30 seconds to form an IZO intermediate film. The IZO intermediate film was then heat-treated in air at 150°C for 5 minutes, and then at 370°C for 1 hour to form an AOS film (IZO film) with a thickness of 6 nm.

[0063] On the IZO film, source / drain (S / D) electrodes (Al, 40 nm) were formed and patterned by thermal evaporation using a metal mask. The IZO film was then patterned using an yttrium aluminum garnet (YAG) laser, and the IZO active layer was obtained by heat treatment at 90°C for 3 hours in air and then slowly cooling to room temperature.

[0064] (Formation of sealing material) On the gate insulating layer with the IZO active layer and S / D electrodes formed, a butyl acetate solution (50mg / mL) containing PMMA (Mw:120,000) was spin-coated at 500rpm for 5 seconds and 4000rpm for 30 seconds, and then heat-treated at 150℃ for 2 hours to form a PMMA layer with a thickness of 100nm. On the PMMA layer, AlOx with a thickness of 40nm was deposited by ALD while keeping the substrate temperature at 110℃ to form a two-layer encapsulation film of PMMA layer / AlOx layer. In this way, a bottom-gate top-contact TFT with an encapsulant and an IZO film was fabricated.

[0065] A schematic cross-sectional view of the fabricated TFT is shown in Figure 4. The fabricated TFT had a channel length (L) of 100 μm and a channel width (W) of 2000 μm.

[0066] Example 2 (Fabrication of TFT with 3-layer encapsulant and IZO) An IZO precursor solution was prepared under the same conditions as in Example 1. On a glass substrate, Cr / Au / Cr were deposited on a pattern formed with photoresist (TLOR, Tokyo Ohka Kogyo Co., Ltd.), and then a Cr / Au / Cr gate electrode with a thickness of 5 / 25 / 5 nm was formed by the lift-off method of removing the photoresist. An AlOx gate insulating film with a thickness of 75 nm was formed using the ALD method.

[0067] The substrate on which the AlOx gate insulating film was formed was treated with a UV ozone cleaner for 10 minutes, and then an IZO film was formed under the same conditions as in Example 1. The formed IZO film was subjected to photolithography using a photosensitive dielectric (PDM, Taiyo Ink Mfg. Co., Ltd.) and wet etching with a 1.75 mass% oxalic acid aqueous solution to form an IZO active layer, which is a patterned n-type semiconductor.

[0068] Then, photolithography was performed using a photosensitive dielectric (PDM, Taiyo Ink Mfg. Co., Ltd.) as a shadow mask to form source / drain S / D electrodes with a thickness of 60 nm by thermal evaporation of Al and lift-off. The laminate with the S / D electrodes formed was then heat-treated in air at 90°C for 3 hours and slowly cooled to room temperature.

[0069] On the gate insulating layer on which the IZO active layer and the S / D electrodes were formed, a butyl acetate solution (5 mg / mL) in which PMMA (Mw: 120,000) was dissolved was spin-coated at 500 rpm for 5 seconds and at 4000 rpm for 30 seconds, and then heat-treated at 150°C for 1 hour to form a PMMA layer with a thickness of 13 nm.

[0070] A 25 nm-thick parylene layer was deposited on the PMMA layer by CVD. A 40 nm-thick AlOx layer was deposited on the parylene layer by ALD while keeping the substrate temperature at 110°C, forming a triple-layer encapsulation film of PMMA layer / parylene layer / AlOx layer. In this way, a bottom-gate top-contact TFT with an encapsulant and an IZO film was fabricated.

[0071] Figure 5 shows a schematic cross-sectional view of the fabricated TFT. Figure 6 shows optical microscope photographs of the fabricated TFT. The fabricated TFT had a channel length (L) of 10 μm and a channel width (W) of 200 μm. Figure 6(a) is an optical microscope photograph of the fabricated TFT observed from above, and Figure 6(b) is an enlarged photograph of the area enclosed in a square in Figure 6(a).

[0072] Comparative Example 1 A TFT was fabricated in the same manner as in Example 2, except that the sealing film was a single PMMA layer having a thickness of 13 nm.

[0073] Comparative Example 2 A TFT was fabricated in the same manner as in Example 2, except that the sealing film was a single parylene layer having a thickness of 25 nm.

[0074] Comparative Example 3 A TFT was fabricated in the same manner as in Example 2, except that the sealing film was a single AlOx layer with a thickness of 40 nm.

[0075] Comparative Example 4 A TFT was produced in the same manner as in Example 2, except that the sealing film was not formed.

[0076] Comparative Example 5 A TFT was fabricated in the same manner as in Example 2, except that the sealing film was a 13 nm thick PMMA layer and a 25 nm thick parylene layer disposed thereon.

[0077] Using a semiconductor parameter analyzer (Keithley 4200-SCS), electrical measurements were performed on the TFTs fabricated in the examples and comparative examples under room temperature and dark conditions. The thicknesses of the IZO film and PMMA layer were measured by X-ray reflectivity measurement (XRR, Rigaku SmartLab, CuKα irradiation, λ=1.5416Å). The surface roughness was measured using an atomic force microscope (AFM, Shimadzu SPM-9700HT). When measuring the characteristics, a through hole was formed in the encapsulant using a YAG laser, and electrical continuity was ensured using silver paste.

[0078] (Evaluation of the impact of the TFT manufacturing process on the performance of the active layer) The transfer characteristics of the TFTs fabricated in Comparative Examples 1 to 4 were measured, and the influence of the TFT fabrication process on the performance of the active layer was evaluated.

[0079] FIG. 7 shows the measurement results of the transfer characteristics of TFTs including the encapsulants of Comparative Example 1 (single PMMA layer), Comparative Example 2 (single parylene layer), and Comparative Example 3 (single AlOx layer), and a TFT including no encapsulant of Comparative Example 4.

[0080] The TFT of Comparative Example 4 (without encapsulant) had a saturation mobility (μ sat ) is 2.3cm 2 V -1 s -1 , on / off current ratio (I on / I off ) is about 10 8, and the threshold voltage (Vth) was 2.0 V. This value was used as the reference value for comparison.

[0081] The TFT of Comparative Example 1 (single layer PMMA) is 2.0 cm 2 V -1 s -1 μ sat , I on / I off ≒10 8 It exhibited desirable characteristics such as a Vth of 1.7 V and negligible hysteresis.

[0082] The TFT of Comparative Example 2 (single parylene layer) exhibited a large negative shift in Vth, which is believed to be due to the long vacuum conditions during parylene deposition and reactive radical species derived from the parylene source that may react with weakly bonded oxygen atoms, which affected the IZO active layer with a non-stoichiometric composition.

[0083] The TFT of Comparative Example 3 (single AlOx layer) exhibited a large negative shift in Vth. Its performance was further deteriorated than that of the TFT of Comparative Example 2 (single parylene layer). This is believed to be due to the harsh conditions of the ALD method, such as high vacuum, high temperature (110°C), and the use of water as a reactive species. Thus, the parylene coating process and the ALD method changed the properties of the IZO active layer, which has a non-stoichiometric composition.

[0084] (Evaluation of three-layer encapsulant) FIG. 8 shows the measurement results of the transfer characteristics of a TFT including the sealing material of Example 2 (three layers of PMMA layer / parylene layer / AlOx layer) and a TFT including no sealing material of Comparative Example 4.

[0085] The TFT of Example 2 exhibited substantially the same characteristics as the TFT of Comparative Example 4. That is, it was confirmed that the PMMA layer / parylene layer double layer functioned as a protective layer during the deposition of AlOx by the ALD method.

[0086] (Evaluation of encapsulant components against moisture) The TFTs of Comparative Example 1 (single layer PMMA), Comparative Example 4 (no encapsulant), and Comparative Example 5 (two layers of PMMA / parylene) were immersed in deionized water for 15 minutes and air-dried (hereinafter referred to as water treatment). The transfer characteristics of each water-treated TFT were measured to evaluate the waterproof characteristics. The evaluation was performed based on the characteristics of the TFT of Comparative Example 4 (no encapsulant) before the water treatment.

[0087] FIG. 9 shows the characteristics of the TFT of Comparative Example 4 (no sealant) before and after water treatment, as well as the characteristics of the TFT of Comparative Example 1 (single layer of PMMA) and the TFT of Comparative Example 5 (two layers of PMMA / parylene) after water treatment.

[0088] In the TFT of Comparative Example 4 (without encapsulant), a large amount of water was mixed into and remained in the back channel layer after the water treatment, which acted as a charge donor and trap, causing a large negative Vth shift and large hysteresis to be observed.

[0089] The TFT of Comparative Example 1 (single layer PMMA) showed a slight Vth shift, but the hysteresis was negligible. The TFT of Comparative Example 5 (two layers of PMMA / parylene) showed substantially the same characteristics as the TFT of Comparative Example 4 (no encapsulant) before water treatment. In other words, it was shown that the PMMA / parylene two-layer has a strong protective ability against moisture, and it is also found to have a protective ability in the film formation process by the ALD method. Due to the low moisture permeability of parylene, the PMMA / parylene two-layer has a better buffer function than the PMMA single layer during AlOx deposition.

[0090] (Evaluation of bias stress stability) The bias stress stability at room temperature (25°C) was evaluated for the TFT of Example 2 (three layers of PMMA layer / parylene layer / AlOx layer), the TFT of Comparative Example 1 (single layer of PMMA), the TFT of Comparative Example 4 (no encapsulant), and the TFT of Comparative Example 5 (two layers of PMMA / parylene). Figure 10 shows the measurement results of the bias stress stability.

[0091] Bias stress stability is the drain current (I D) was measured, and the I D The rate of decrease was calculated and evaluated.

[0092]

number

[0093] When the gate bias is constant, I D There was a tendency for the value to gradually decrease. This is due to the following formula: O2(g)+e - (s)=2O - (s) This is believed to be because the absorbed oxygen was able to steal electrons from the conductive bonds, as shown by

[0094] The TFT of Comparative Example 4 (without encapsulant) was D The decrease rate was 67%, and the stability of the bias stress was the worst. D The decrease rate was 21%, and the I of the TFT of Comparative Example 5 (PMMA / parylene two-layer) D The rate of decrease was suppressed to 17%. In particular, in the TFT of Example 2 (three layers of PMMA layer / parylene layer / AlOx layer), I D The rate of decline has been significantly reduced, and I D The decline was 2%.

[0095] (Evaluation of Vth shift before and after bias stress) The transfer characteristics were measured before and after bias stress for the TFT of Example 2 (three layers of PMMA layer / parylene layer / AlOx layer), the TFT of Comparative Example 1 (single layer of PMMA), the TFT of Comparative Example 4 (no encapsulant), and the TFT of Comparative Example 5 (two layers of PMMA / parylene), and the Vth shift value (ΔVth) was estimated. Figure 11 shows the measurement results of the transfer characteristics before and after bias stress.

[0096] As shown in FIG. 11(a), the ΔVth of the TFT of Comparative Example 4 (without encapsulant) was 2.8 V. As shown in FIG. 11(b), the ΔVth of the TFT of Comparative Example 1 (single layer PMMA) was 0.7 V. As shown in FIG. 11(c), the ΔVth of the TFT of Comparative Example 5 (two layers of PMMA / parylene) was 0.8 V. As shown in FIG. 11(d), the ΔVth of the TFT of Example 2 (three layers of PMMA layer / parylene layer / AlOx layer) was suppressed to 0.2 V. This is because the IZO active layer was not damaged when the AlOx film was formed by the ALD method due to the barrier effect of the PMMA / parylene buffer layer.

[0097] (Evaluation of the effect of two-layer sealing material) FIG. 12 shows the measurement results of the transfer characteristics of a TFT including the encapsulant of Comparative Example 5 (two layers of PMMA / parylene) and a TFT including no encapsulant of Comparative Example 4.

[0098] Compared with the TFT of Comparative Example 4 (no encapsulant), the TFT of Comparative Example 5 (two layers of PMMA / parylene) showed little change. Figure 13 shows the results of measuring the X-ray reflectivity of the PMMA layer formed under the same conditions as Comparative Example 5. It can be seen that the IZO active layer, which has a nonstoichiometric composition, was effectively protected from radicals during parylene deposition, even though the PMMA layer was only 13 nm thick.

[0099] Fig. 14 shows an AFM measurement image of an IZO layer produced under the same conditions as in Example 1. Fig. 15 shows an AFM measurement image of a PMMA layer formed on an IZO layer produced under the same conditions as in Example 1. The surface roughness RMS of the IZO layer was 0.196 nm, and the PMMA layer formed on the IZO layer had a flat structure without pinholes and a surface roughness RMS of 0.334 nm.

[0100] (Analysis of oxygen defect concentration distribution) Fig. 18 shows the results of angle-resolved XPS measurement of O1s of an AOS layer (IZO film) prepared by the same method as in Example 1. Fig. 18(a) is a graph summarizing the measurement spectrum of O1s of the AOS layer when the tilt angle θ is set to 0°, 40°, 55°, 63°, and 70°. Fig. 18(b) to Fig. 18(f) are graphs obtained by decomposing and fitting the measurement spectrum measured at the tilt angle θ of 0°, 40°, 55°, 63°, and 70° into MOM having a peak at binding energy 529.7 eV, MO(H) having a peak at 531.1 eV, and MOR having a peak at 532.0 eV.

[0101] M stands for In or Zn. MOM stands for oxygen bridging between metal centers, and refers to an oxide with a stoichiometric composition with no oxygen vacancies. MO(H) stands for oxygen or hydroxyl group with an unpaired electron that does not bridge between metal centers, and MOR stands for oxygen in organic matter such as H2O, CO2, or alcohol that is bonded to a metal center, and each stands for a composition with oxygen vacancies.

[0102] Figures 19 and 22 and Table 1 show the ratio of MOM (metal oxide state) to the total O1s calculated by the above fitting (η M-O-M ) is shown as an angle dependence.

[0103] [Table 1]

[0104] The larger the tilt angle θ, the more surface selective it becomes, and the closer the composition to the surface of the AOS layer is, the higher the MOM bond ratio is. The ratio of MOM bonds is constant at about 50% inside the AOS film, but the ratio of MOM bonds decreases toward the surface of the AOS film, decreasing to about 40%, i.e., the ratio of MOM bonds decreased by about 20%. Thus, it was shown that the AOS layer has more oxygen defects near the surface than inside, and has a non-uniform chemical composition in the film thickness direction. In Figure 22, the three points at 5.5 nm on the horizontal axis represent the ratio of the integrated value of each MO species from the outermost AOS surface to a depth of 5.5 nm, and the three points at 2.8 nm represent the ratio of the integrated value of MO species from the outermost surface to a depth of 2.8 nm.

[0105] (Evaluation of characteristics after long-term storage) 23 shows a graph evaluating the initial characteristics measured immediately after fabrication and the characteristics after being left in air for 20 months for the TFT device with W / L=200 μm / 10 μm fabricated in Example 2. Although some changes were observed after being left for 20 months, the initial characteristics and the characteristics after being left for 20 months were essentially the same, indicating that the device has good long-term stability. [Explanation of symbols]

[0106] 100 Encapsulating material 10 Polymer Layer 12 First polymer layer 14 Second polymer layer 20 Inorganic oxide insulating layer 30 Compound layer with non-stoichiometric composition

Claims

1. A sealing material for a compound having a non-stoichiometric composition, comprising: a polymer layer that can be disposed on the compound having a non-stoichiometric composition; and an inorganic oxide insulator layer on the polymer layer opposite the non-stoichiometric compound; Including, the polymer layer includes a first polymer layer including an organic solvent soluble polymer, and a second polymer layer located between the first polymer layer and the inorganic oxide insulator layer; The second polymer layer is made of a chemical vapor deposition film. Encapsulant for compounds with non-stoichiometric composition.

2. The encapsulant of claim 1 , wherein the first polymer layer, the second polymer layer, and the inorganic oxide insulator layer have a combined thickness of 100 nm or less.

3. The encapsulant according to claim 1 or 2, wherein the organic solvent-soluble polymer is an acrylic polymer, a styrene polymer, a fluorine-based polymer, a thermally crosslinkable polymer, or a combination thereof.

4. The encapsulant according to any one of claims 1 to 3, wherein the inorganic oxide insulator of the inorganic oxide insulator layer is AlOx, HfOx, ZrOx, SiOx, TiOx, or a combination thereof.

5. The encapsulant according to any one of claims 1 to 4, wherein the chemical vapor deposition film is parylene.

6. The sealing material according to any one of claims 1 to 5, wherein the compound having a non-stoichiometric composition is an amorphous metal oxide inorganic semiconductor film.

7. 7. The encapsulant according to claim 6, wherein the amorphous metal oxide inorganic semiconductor film has a different distribution of oxygen vacancies in a direction perpendicular to a main surface of the film, with the surface having more oxygen vacancies than the interior.

8. An electronic device comprising the encapsulant according to any one of claims 1 to 7.

9. Preparing a substrate; preparing an organic solvent having a first polymer dissolved therein; applying an organic solvent having the first polymer dissolved therein onto the substrate to form a polymer layer including a first polymer layer; and On the polymer layer, an inorganic oxide insulator layer is formed by atomic layer deposition or sputtering to obtain an encapsulant. Including, forming the polymer layer includes forming a second polymer layer, the second polymer layer being a chemical vapor deposition film, on the first polymer layer using a chemical vapor deposition method; forming the inorganic oxide insulator layer includes forming the inorganic oxide insulator layer on the second polymer layer. A method for producing a sealing material for a compound having a non-stoichiometric composition.

Citation Information

Patent Citations

  • Sealed device

    JP2010093172A

  • Transistor and display device

    JP2011086923A

  • Organic thin film transistor and organic thin film light-emitting transistor

    WO2007094361A1